1997
DOI: 10.2514/2.4145
|View full text |Cite
|
Sign up to set email alerts
|

Reformulation of Edelbaum's Low-Thrust Transfer Problem Using Optimal Control Theory

Abstract: The problem of optimal low-thrust transfer between inclined orbits is reformulated within the framework of optimal control theory. The original treatment considered the time-constrained inclination maximization with velocity as the independent variable allowing the use of the theory of maxima. Because the independent variable is double valued for some transfers, two expressions for the inclination change involving inverse-sine functions are needed to describe all possible transfers. The present analysis casts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 4 publications
(4 reference statements)
0
40
0
Order By: Relevance
“…The average orbital semimajor axis can be used to replace the osculating one in Eq. (10). For the phasing mission, the average orbital semi-major axis of the anti-tangential thrust duration should be same as that of the tangential thrust duration, which can be estimated as…”
Section: Circular Orbit Phasingmentioning
confidence: 99%
See 1 more Smart Citation
“…The average orbital semimajor axis can be used to replace the osculating one in Eq. (10). For the phasing mission, the average orbital semi-major axis of the anti-tangential thrust duration should be same as that of the tangential thrust duration, which can be estimated as…”
Section: Circular Orbit Phasingmentioning
confidence: 99%
“…Edelbaum suggested that changing station using tangential thrust is the most effective approach [4]. On the basis of Edelbaum's approach, the trajectory from one circular orbit to another is optimized under the assumption of quasi-circular orbits [2,10,13]. In addition, the phasing mission between different orbits has been investigated by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…All of these analyses assume that the orbit remains circular after each cycle or revolution. In reference [9], the original Edelbum theory is revisited by extending, completing, and deriving the yaw steering expressions without ambiguity and recasting the theory within the framework of optimal control for minimum time. In reference [10], the authors reexamine Edelbum's approach and some improvements are introduced, while maintaining the assumption of quasi-circular orbits.…”
Section: Shafieenejad and A B Novinzadehmentioning
confidence: 99%
“…In other words, system equation (24) is autonomous and the Hamiltonian is a constant. Finally, this constant must be zero because final time is unspecified [9,11] …”
Section: Minimum-time Low-thrust Orbital Transfermentioning
confidence: 99%
“…A systematic mathematical representation of these problems is considered. T HE optimization problem of continuous-thrust spacecraft trajectories has been studied extensively [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The optimization methods for the trajectories have been mainly of two types: indirect and direct techniques or their combinations.…”
mentioning
confidence: 99%